Blade runner, de 2019 a 2049. O filme da ficção científica como divulgador da ciência - Marín Ramos, Esther (InMediaciones de la Comunicación, 2018)
It’s been 35 years since the premiere of Blade Runner (Ridley Scott, 1982) until the arrival of its sequel Blade Runner 2049 (Villeneuve, 2017). This gives us the opportunity to prove to what extent how changes in our culture modified the discourse of one of the best science fiction films that, with greater emphasis, represented the fear of the adverse effects of progress. In the present article, both films will analyzed from a comparative perspective using theoretical concepts from the sociology and communication studies. One of the results shows that the apocalyptic alarmism, a main characteristic of the genre in the past century, has given place to a more lucid and complete vision of the risks. But also the possibilities and dilemmas that awakens the techno-scientific advance and establishes the science-fiction genre as a valuable resource for its reflection and dissemination.